Design of a Web-Based Personnel Administration Management Information System at Politeknik Piksi Ganesha - Iksan, Muhamad Zaenal; Abdussalaam, Falaah Abdussalaam (Politeknik Piksi Ganesha Indonesia, 2023)
The background of this research is that the management of personnel administration at the Piksi Ganesha Polytechnic campus still uses conventional methods, is considered not optimal, and is very prone to viruses and data loss. In this study, the authors used a qualitative research method with a descriptive approach. In contrast, the software development method used was the Prototyping Method using the Unified Modeling Language (UML) system modeling, which was applied using the PHP programming language with the Laravel framework and MYSQL database. This study resulted in a web-based Personnel Administration Management Information System or Personnel Information System (SIMPEG), which has features starting from automatic employee data management, centralized employee filing, and integrated attendance with validation of devices in the campus's Public IP network. It can be accessed on mobile by employees.